Comparative study on the effect of various pretreatment methods on the enrichment of hydrogen producing bacteria in anaerobic granulated sludge from brewery wastewater - Mohammadi, P.; Ibrahim, S.; Annuar, M.S.M. (2012)
Five pretreatment methods, namely chemical, acid, heat-shock, freezing and thawing, and base, were evaluated for the enrichment of hydrogen-producing bacteria in anaerobic granulated sludge, which will be subsequently used as seed in biological hydrogen production. All the pretreatments showed positive effects towards improving hydrogen (H 2) generation by the microbial population with higher hydrogen production yield and COD removal efficiency as compared to control. The granulated sludge pretreated by heat-shock showed maximum accumulated H 2 (19.48mLg -1-COD), COD removal efficiency (62), and biomass concentration (22.5 gL -1). Â© 2012 Korean Institute of Chemical Engineers, Seoul, Korea.